Symmetry in Many-Body Physics - Yukalov, V.I; S. Bagnato, V.; Nazmitdinov, Rashid G. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains 14 articles on various aspects of many-body physics. Most of the articles are devoted to different phenomena in Bose-Einstein condensate (M.R. Pathak and A. Nath; M.H. Figlioli Donato and S.R. Muniz ; B. Halder with coauthors; O.E. Alon).L. Madeira and V.S. Bagnato discuss the route of an out-of-equilibrium system to its thermalized state. M.R. Singh discusses the many-body interactions in plasmonic nanohybrids. M. Pudlak and R. Nazmitdinov analyze electron transport through a one-dimensional quantum ring, subject to Rashba spin-orbit interaction in the presence of external fields. R. Friedberg and J.T. Manassah report computer investigations on the duration memory for storage for an isolated atom. M.C. Pagnacco with coauthors describe the crazy-clock phenomenon. V.I. Yukalov and E.P. Yukalova consider materials with nanoscale phase separation. E.M. Anitas investigates materials with fractal-like geometry. L. Madeira with coauthors address the topic of quantum turbulence. K. Ziegler discusses how the employment of the diagonal elements of the time correlation matrix can be used to probe closed quantum systems that are measured at random times. L. Salasnich analyzes the collective dynamics of electrons in graphene positioned between the two slabs.